The anomalous correlation: examining project-based learning's impact on final examination performance - Abu Hassan, Fatin Zahida; Mat Russ, Nazirah; Bahrom, Suhaila (Asian Scholars Network (ASNet), 2025)
Project-Based Learning (PBL) is widely recognised as a transformative educational approach, offering solutions to challenges posed by traditional teaching methods. Its benefits have been extensively documented within the education sector. However, despite its acclaim, studies have revealed a tenuous link between PBL and students' final examination performance. Hence, this research aims to assess the impact of PBL on final examination results, employing a mixed-methods approach. The study involved 173 participants enrolled in Introduction to Statistics for Built Environment at CFSIIUM. Data collection encompassed final examination scores and peer assessment surveys, which were analysed using Pearson’s Correlation Coefficients. Thematic analysis was employed to interpret qualitative insights from peer assessments. The findings reveal a weak positive correlation (r = 0.207, p = 0.006) between PBL implementation and final examination performance. Thematic analysis of the challenges associated with PBL, including issues with student participation and commitment, communication, task management and quality control, timing and availability sheds light on factors influencing individual outcomes. While PBL holds promise for enhancing students’ performance and fostering experiential learning and knowledge retention, strategic planning and careful consideration are imperative for maximizing its benefits and mitigating potential drawbacks. These insights are expected to inform pedagogical strategies and driving enhancements in PBL-driven learning experiences.